Home-administered pre-surgical psychological intervention for knee osteoarthritis (HAPPiKNEES): study protocol for a randomised controlled trial - das Nair, Roshan; Anderson, Pippa; Clarke, Simon; Leighton, Paul; Lincoln, Nadina; Mhizha-Murira, Jacqueline R.; Scammell, Brigitte E.; Walsh, David A. (BioMed Central, 2016)
Background